Transformasi Dakwah Islam di Minangkabau: Kontinuitas Tradisi dan Gerakan Pembaruan - Sarwan Sarwan; Alwa Hidul Kohar; Ferdian Yordan (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2026)
This study explores the dynamics of Islamic da‘wah in Minangkabau within a historical trajectory, beginning with the initial process of Islamisation and extending to the emergence of reformist movements such as the Kaum Padri and Kaum Muda. Islamic da‘wah in Minangkabau was not merely a matter of religious propagation; it also constituted a complex socio-cultural transformation. The early phase of Islamisation occurred peacefully through trade routes, networks of ‘ulama, and traditional religious institutions such as the surau. A central figure in this phase was Shaykh Burhanuddin of Ulakan, who played a pivotal role in laying the foundations of Sufi-oriented da‘wah through the development of the Shattariyah order. In the nineteenth century, the Kaum Padri movement emerged, advocating Islamic purification through radical approaches. This was followed in the early twentieth century by the Kaum Muda, who emphasised rationalism, modern education, and religious reform. The research employs a qualitative approach with a case study design and thematic analysis of secondary sources, including scholarly books and journal articles. The findings indicate that the Islamisation of Minangkabau was a gradual and acculturative historical process, marked by both tensions and syntheses between Islamic law (sharī‘a) and local custom (adat). The principle “Adat basandi syarak, syarak basandi Kitabullah” (Custom is founded upon Islamic law, and Islamic law upon the Qur’an) reflects the successful integration of Islamic values with local culture. This study underscores Minangkabau’s strategic role in shaping the character of Islamic da‘wah in the Malay-Indonesian world.